Meta-Analisis: Pengaruh Substitusi Jagung dengan Bahan Pakal Lokal Terhadap Kualitas Karkas Daging Broiler - Danung Nur Adli; Osfar Sjofjan (Politeknik Negeri Jember, 2020)
The purpose of this study was to determine the effect of substitution of corn with local ingredients on the quality of broiler meat using meta-analysis technique. This study used meta-analysis technique to integrate 55 data from 9 journals that contain information about replacing corn with local feedstuffs. The meta-analysis technique begins with collecting data from several scientific publications that contain tannin and saponin levels. Furthermore, the data was tabulated in the form of database with the help of microsoft excel, in this tabulation process the units of each data are equalized, after that the data was tabulated and analyzed using comprehensive meta-analysis version 3. The effect of corn replacement on the quality of broiler meat was not significant, this can be seen on the content of the percentage of carcasses, carcass weights, and cholesterol of meat was not different. The results show that the distance between the given model and the actual model indicates that there was decrease in the amount of cholesterol in meat with the replacement of corn in feed ingredients (0.05<P<0.1). The conclusion from the results of this meta-analysis was that the replacement of corn does not improve the quality of the broiler carcass.